Application of the China Meteorological Assimilation Driving Datasets for the SWAT Model (CMADS) in East Asia - Meng, Xianyong (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
To promote scientific understanding of surface processes in East Asia, we have published details of the CMADS dataset in the journal, Water, and expect that users around the world will learn about CMADS datasets while promoting the development of hydrometeorological disciplines in East Asia. We hope and firmly believe that scientific development in East Asia and our understanding of this typical region will be further advanced.